Hypertonicity-enforced BCL-2 addiction unleashes the cytotoxic potential of death receptors - Sirtl, Simon; Knoll, Gertrud; Dieu Thuy Trinh,; Lang, Isabell; Siegmund, Daniela; Gross, Stefanie; Schuler-Thurner, Beatrice; Neubert, Patrick; Jantsch, Jonathan; Wajant, Harald; Ehrenschwender, Martin (Oncogene, 2018)
Attempts to exploit the cytotoxic activity of death receptors (DR) for treating cancer have thus far been disappointing. DR activation in most malignant cells fails to trigger cell death and may even promote tumor growth by activating cell death-independent DR-associated signaling pathways. Overcoming apoptosis resistance is consequently a prerequisite for successful clinical exploitation of DR stimulation. Here we show that hyperosmotic stress in the tumor microenvironment unleashes the deadly potential of DRs by enforcing BCL-2 addiction of cancer cells. Hypertonicity robustly enhanced cytotoxicity of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) and other DR ligands in various cancer entities. Initial events in TRAIL DR signaling remained unaffected, but hypertonic conditions unlocked activation of the mitochondrial death pathway and thus amplified the apoptotic signal. Mechanistically, we demonstrate that hyperosmotic stress imposed a BCL-2-addiction on cancer cells to safeguard the integrity of the outer mitochondrial membrane (OMM), essentially exhausting the protective capacity of BCL-2-like pro-survival proteins. Deprivation of these mitochondrial safeguards licensed DR-generated truncated BH3-interacting domain death agonist (tBID) to activate BCL-2-associated X protein (BAX) and initiated mitochondrial outer membrane permeabilization (MOMP). Our work highlights that hyperosmotic stress in the tumor environment primes mitochondria for death and lowers the threshold for DR-induced apoptosis. Beyond TRAIL-based therapies, our findings could help to strengthen the efficacy of other apoptosis-inducing cancer treatment regimens.
EVALuna2:34786